Immune thrombocytopenia: clinical manifestation and therapy response. The interim analysis of Russian register of patients with primary immune thrombocytopenia and literature review - I. A. Lisukov; A. A. Maschan; A. V. Shamardina; T. V. Chagorova; I. L. Davydkin; T. M. Sycheva; T. P. Zagoskina; E. V. Karyagina; G. N. Salogub; M. T. Savinova; T. V. Shelekhova; L. G. Kovaleva; et al. (Онкогематология, 2014)
Primary immune thrombocytopenia (ITP) is a rare (orphan) blood disease. Most frequent manifestations of ITP are purpura, petechiae and bleedings with many patients have either no symptoms or minimal bleedings manifestation. The management of ITP varies widely and must be based on current international recommendations and individual assessment of clinical course. The paper presents the results of interim analysis of clinical course and therapeutic approaches in the Russian register of ITP patients with immune thrombocytopenia and literature review about ITP treatment approaches.